2014
DOI: 10.1016/j.sab.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Use of gradient dilution to flag and overcome matrix interferences in axial-viewing inductively coupled plasma-atomic emission spectrometry

Abstract: Despite the undisputed power of inductively coupled plasma-atomic emission spectrometry (ICP-AES), its users still face serious challenges in obtaining accurate analytical results. Matrix interference is perhaps the most important such challenge. Dilution of a matrix-containing sample is a common practice to reduce matrix interference. However, determining the optimal dilution factor requires tedious and time-consuming offline sample preparation, since emission lines and the effect of matrix interferences are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…11 More recently, a gradient dilution method that overcomes matrix interferences in ICP OES has been described. 12 This approach uses an HPLC pump to dilute the sample provided to the ICP while monitoring two emission lines continually. This allows an automated approach to finding the highest sample concentration where the matrix effects are minimized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 More recently, a gradient dilution method that overcomes matrix interferences in ICP OES has been described. 12 This approach uses an HPLC pump to dilute the sample provided to the ICP while monitoring two emission lines continually. This allows an automated approach to finding the highest sample concentration where the matrix effects are minimized.…”
mentioning
confidence: 99%
“…The same research group has described a manifold for calibration in flow injection analysis, and also a technique for flow injection gradient titration . More recently, a gradient dilution method that overcomes matrix interferences in ICP OES has been described . This approach uses an HPLC pump to dilute the sample provided to the ICP while monitoring two emission lines continually.…”
mentioning
confidence: 99%
“…A drawback of this method is that the intensity-ratio profile is less sensitive to changes in plasma conditions (and therefore to the presence of a matrix interference) than is the spatial emission profile. We have shown [17] that a 10% change in solvent composition can cause significant matrix effects. Unfortunately, the intensity-ratio method was not able to flag this error.…”
Section: Introductionmentioning
confidence: 93%
“…and standard additions [10][11][12][13]) must be used to correct for matrix interference, among which dilution is one the most common [14][15][16]. A previous study [17] by our research group showed that the intensity ratio of two emission lines (from the same or different elements) can be used as a matrix-effect indicator when the sample is progressively diluted by means of a gradient high-performance liquid chromatography (HPLC) pump. Due to a disparity in the upper-state energies of two emission lines, the effect of the progressively diluted matrix on these emission lines is different.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, from the same ratio profile employed to detect a matrix effect, one can also locate the optimal dilution factor for the minimization of interference. This gradient-pump method was first developed to flag and correct matrix interference in ICP-OES 22 with encouraging results. The present study builds on the previous work, expanding its application to flag and correct for interferences within ICP-MS. Of course, prolonging analysis time is not ideal for routine analysis despite its benefits; however, this gradient-dilution run need be performed on only a single sample among a batch of samples with similar matrices.…”
Section: Introductionmentioning
confidence: 99%